The Intricacies of The Salafiyyah’s Belief in Carsh (Throne) as Contained in The Qur’Ᾱn - Gambari, Yusuph Dauda (Al-Hikmah, 2023)
cArsh, in relation to Allah, is one of the issues generating diverse views among scholars of different blocs in Islam. This is because it is mysterious. The Salafiyyah enclave is one of the key actors whenever topics relating to the Being of Allah and His CArsh came up for discussion. Therefore, this paper aims to examine the various submissions of the Salafiyyah scholars on cArsh to bring out the disparities and their implications. The interpretive method is adopted for proper and adequate assessment of related issues. The findings of this paper revealed that there is no common ground among the Salafiyyah when it comes to cArsh and the Being of Allah and that it constitutes part of Mutashābihāt (allegorical issues) that Q.3:7 directed the Muslims to keep off discussions on them. It also revealed that some Salafiyyah scholars are equally guilty of anthropomorphism and have accused many scholars of other blocs. The paper, therefore, concluded that Tafwīḍ ’l-Macnā wan-Nafyyu ’l-Kayf (abstinence from explanation and negation of likeness) is what the Salaf and majority of the scholars held on to and advocated, either in relation to cArsh or allegorical issues in Islam. It is therefore recommended that contemporary Muslims should limit themselves to what is stated in both the Qur’ān and authentic ḥadīth with regards to Mutashābihāt without explaining their modality or rejection of them.